THE GAP ANALYSIS OF DEVELOPMENT BETWEEN REGENCY OR CITY IN THE PROVINCE OF NORTH SUMATRA FOR THE PERIOD 2004-2008 - Muhammad Yusuf (Universitas Negeri Medan, 2013)
One of the main functions of the government of North Sumatra Province is how to reduce the gap between the district / city in the province of North Sumatra. A regional disparity is the ratio of real per capita income among regions with per capita real income of the province. This study aims to analyze the development gap among districts / cities in North Sumatra. In addition, this study also analyzes the Klasen typology at each district / city in North Sumatra. The data’s that used in this study are secondary data from BPS report, North Sumatra in Figures 2004-2008 period. Data were analyzed using descriptive methods to illustrate how the levels of inequality and Klasen typology each district / city in North Sumatra. To see the inequality index formula used Williamson (Vw) and to see Klasen typology by dividing the area into developed areas, developed pressure, developed and underdeveloped. The research result shows that there is no gap between districts / cities in North Sumatra, where the index values approaching Williamson zero, and Medan is the only city that has a value field Williamson index of 0.314, while other areas close to zero.The districts / cities in North Sumatra has a category 4 classes according to Klasen typology the developed areas, developed pressure, developed and underdeveloped regions. The Medan city including developed areas and has the highest disparity of 0.314.The implication of this research is the need to accelerate policy development with the help of the central government.